2023
DOI: 10.30534/ijeter/2023/021192023
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review of Rehabilitation Wearable Robots for the Upper and Lower Limbs

Abstract: Many diseases, such as stroke, physical disability in the elderly, work injuries, and sports injuries can lead to weak limbs. Stroke is one of the main reasons for long-range disability, especially upper limb disability, that affects the activities of daily living (ADL) of individuals. Rehabilitation, such as manually assisted training or physical therapy that involves repeatedly moving the affected limb, is one of the most successful ways to reduce the effects of stroke. However, patients may be prevented fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Often, exoskeletons adopt a wearable configuration, as shown in Figure 10. Wearable exoskeletons are electromechanical devices designed to assist, augment, or enhance motion and mobility in the wrist [19]. Occasionally, wearable exoskeletons can use pneumatic elements like pneumatic muscles, which have the potential to create a more compliant interaction with the patient.…”
Section: Wrist Rehabilitation Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, exoskeletons adopt a wearable configuration, as shown in Figure 10. Wearable exoskeletons are electromechanical devices designed to assist, augment, or enhance motion and mobility in the wrist [19]. Occasionally, wearable exoskeletons can use pneumatic elements like pneumatic muscles, which have the potential to create a more compliant interaction with the patient.…”
Section: Wrist Rehabilitation Classificationmentioning
confidence: 99%
“…It should be noted that the review articles found in the literature do not have the wrist as their main focus, covering other joints of the upper and lower limbs [3,4,[19][20][21][22] or are not up-to-date [1]. The review articles [1,3,4,[19][20][21][22] also do not clearly present how to conduct the mathematical modeling of the new device based on the characteristics of the human wrist as detailed in this paper.…”
Section: Introductionmentioning
confidence: 96%